Spatially inhomogeneous periodic solutions in distributed Hutchinson equation - D. S. Glyzin; S. A. Kaschenko; A. S. Polstyanov (Моделирование и анализ информационных систем)
The asymptotics of spatially inhomogeneous periodic solutions of the complex spatially distributed Hutchinson equation with periodic boundary conditions are presented. It is shown that such solutions are observable in a numerical experiment.